2020
DOI: 10.4238/gmr18418
|View full text |Cite
|
Sign up to set email alerts
|

Research Article Variability of <i>Myrciaria</i> <i>dubia</i> genotypes (Myrtaceae) in native populations of Roraima state

Abstract: Camu-camu, Myrciaria dubia (Myrtaceae) is a native species of the Amazon Rainforest that has been attracting attention worldwide and arousing great interest in the food and pharmacological industries due to the high concentrations of ascorbic acid in its fruit, which is exported to several countries. Characterizing different materials of M. dubia by means of molecular markers allows integration of agronomic and molecular information to aid in the search for more promising varieties. We examined the genetic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
0
0
Order By: Relevance
“…Germplasm collections with specimens from all the Amazon basin are active in Brazil at INPA (Instituto Nacional de Pesquisa da Amazônia) and EMBRAPA, with ex-situ collections in Manaus, Belem and Boa Vista (Nascimento et al, 2013;Sakazaki et al, 2022;Yuyama & Valente, 2011), and in Peru at IIAP (Instituto de Investigaciones de la Amazonía Peruana) from western Amazonia (Pinedo-Panduro et al, 2020;Šmíd et al, 2017). Genetic studies have shown a high intra-and inter-population variability with a high geographic structure (Nunes et al, 2017, Rojas et al, 2011Šmíd et al, 2017;Souza et al, 2020), which indicates that to conserve the existing genetic diversity it will be needed to sample at large geographic scales.…”
Section: Introductionmentioning
confidence: 99%
“…Germplasm collections with specimens from all the Amazon basin are active in Brazil at INPA (Instituto Nacional de Pesquisa da Amazônia) and EMBRAPA, with ex-situ collections in Manaus, Belem and Boa Vista (Nascimento et al, 2013;Sakazaki et al, 2022;Yuyama & Valente, 2011), and in Peru at IIAP (Instituto de Investigaciones de la Amazonía Peruana) from western Amazonia (Pinedo-Panduro et al, 2020;Šmíd et al, 2017). Genetic studies have shown a high intra-and inter-population variability with a high geographic structure (Nunes et al, 2017, Rojas et al, 2011Šmíd et al, 2017;Souza et al, 2020), which indicates that to conserve the existing genetic diversity it will be needed to sample at large geographic scales.…”
Section: Introductionmentioning
confidence: 99%